RELATIONSHIP BETWEEN KNOWLEDGE AND NUTRITION STATUS OF PREGNANT ADOLESCENTS IN ADJUMANI TOWN COUNCIL. A CROSS-SECTIONAL STUDY. - Serwambala, Charles; Nalubega, Jane Frank; Kungu, Joseph (Student's Journal of Health Research Africa, 2024)
Background Adolescent pregnancy is the incidence of pregnancy in females aged 10-19. The study aims to assess the relationship between knowledge, Attitude, and nutrition status of pregnant adolescents in Adjumani Town Council. Methodology A cross-sectional study consisting of 288 pregnant adolescents was conducted. Data was collected on socio-demographic variables, nutritional knowledge, attitudes, practices, and nutrition status indicators such as BMI. Pearson correlation was used to establish relationships between variables. Results 41.7% (120/288) had a primary level of education and the majority 33.3% (98/288) were farmers. The Pearson correlation between dietary attitude and nutritional status was 0.007, indicating a negligible relationship. The p-value is 0.906, indicating no significant association between dietary attitude and nutritional status. The regression coefficient for nutrition knowledge is (B=-0.039, SE=0.058, β=-0.038, t=-0.686 and p=0.493). This indicates that nutrition knowledge is not a significant predictor of nutritional status. The regression coefficient for dietary attitude is (B=0.009, SE=0.056, β=0.009, t=0.154, and p=0.878), indicating that dietary attitude is not a significant predictor of nutritional status. Conclusions The majority of the pregnant adolescents had low nutrition knowledge, and were underweight high educational status was associated with good nutritional understanding. Recommendations The findings highlight the need for targeted nutritional education and counseling support to educate adolescents on the importance of a balanced diet and how to make healthier food choices within their means.